The ecology of interrelation of helminthes fauna with the normal bacterial flora of stomachic-intestinal channel of sheep and goats - R. Kh. Gairabekov (Юг России: экология, развитие)
Helminths are wide spread among agricultural animals. They bring huge damage to stockbreeding decreasing of production, and in some case bring out ruin of animals. The preparation using against, helminth are disturbing bacterial flora of stomatic and intestinal track of animals.